Humanização e educação integral refletindo sobre as rotas alternativas - Bataglia, Patrícia Unger Raphael (Editora Oficina Universitária, 2020)
This work is a publication of the Group of Research and Studies in Moral Psychology and Integral Education - GEPPEI and of guests who bring theoretical discussions and reports of innovative practices in education. Each part brings together a set of chapters. In the first part, horizons are contemplated for the paths in search of the re-signification of educational practices, from different points of view based on the presentation and construction of correlations between theories of Jean Piaget, Rudolf Steiner, Paulo Freire, among others. In the second part, the authors traced new routes that were built from experiences initiated by the desire for change and with little certainty of what would happen along the way. The reports show that with theoretical foundation, courage, initiative and perseverance it was possible to build many exciting and motivating stories for the re-signification of education. The experiences presented were elaborated based on principles that contemplate the objectives of re-signification of education, they show us that in the day-to-day, it is possible to build practices that prioritize the participation of all, with respect to individual differences, and with the establishment of spaces for the collective, cooperative and meaningful construction for all those involved in the process of formation for autonomy. Practices begin with a desire for change, not only in the school environment, but in society as, by developing critical capacity, they will be able to exercise citizen participation in the construction of a plural and democratic society.